Tinjauan Literatur tentang Strategi Inovatif dalam Menangani Kebakaran pada Kendaraan Listrik - Supri Supri (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2023)
Electric Vehicles are vehicles that operate entirely or partially on electric motors, utilizing electrical energy stored in batteries or other rechargeable energy storage sources. The increasing use of electric vehicles also brings potential risks of new types of accidents, different from those associated with conventional internal combustion engine vehicles. Therefore, there is an urgent need to provide accurate information and appropriate handling related to electric vehicle technology, including hazard potential assessment, optimization of firefighting basics, selection of suitable firefighting agents, and the development of electric vehicle firefighting application methods. This study aims to understand the handling of electric vehicle fires using a literature review method on 10 research articles. The results show that 6 studies used water as a firefighting agent either alone or in combination with other agents such as CO2, C₆F₁₂O, liquid nitrogen, foam, and fire blankets, making it more effective in extinguishing electric vehicle fires. However, one study does not recommend using water due to its environmental impact when extinguishing electric vehicle fires. The research findings indicate the need for further innovation and research in safety technology and firefighting for electric vehicles.